CD4+ T Cell-Dependent Macrophage Activation Modulates Sustained PS Exposure on Intracellular Amastigotes of Leishmania amazonensis - Wanderley, Joao Luiz Mendes; Deolindo, Poliana; Carlsen, Eric; Portugal, Arieli Bernardo; DaMatta, Renato Augusto; Barcinski, Marcello Andre; Soong, Lynn (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmania amazonensis amastigotes can make use of surface-exposed phosphatidylserine (PS) molecules to promote infection and non-classical activation of macrophages (MΦ), leading to uncontrolled intracellular proliferation of the parasites. This mechanism was quoted as apoptotic mimicry. Moreover, the amount of PS molecules exposed on the surface of amastigotes correlates with the susceptibility of the host. In this study, we tested whether host cellular responses influence PS expression on intracellular amastigotes. We found that the level of PS exposure on intracellular amastigotes was modulated by CD4+ T cell and MΦ activation status in vitro and in vivo. L. amazonensis infection generated a Th1/Th2-mixed cytokine profile, providing the optimal MΦ stimulation that favored PS exposure on intracellular amastigotes. Maintenance of PS exposed on the parasite was dependent on low, but sustained, levels of nitric oxide and polyamine production. Amastigotes obtained from lymphopenic nude mice did not expose PS on their surface, and adoptive transfer of CD4+ T cells reversed this phenotype. In addition, histopathological analysis of mice treated with anti-PS antibodies showed increased inflammation and similarities to nude mouse lesions. Collectively, our data confirm the role of pathogenic CD4+ T cells for disease progression and point to PS as a critical parasite strategy to subvert host immune responses.